Advances in Smart Vehicular Technology, Transportation, Communication and Applications Proceeding of the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, October 25-28, 2018 Mount Emei, China, Part 1 - Ni, Shaoquan; Wu, Tsu-Yang.; Chang, Tang-Hsien.; Pan, Jeng-Shyang.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights papers presented at the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications (VTCA 2018), which was held at Mount Emei, Sichuan Province, China from 25 to 28 October 2018. The conference was co-sponsored by Springer, Southwest Jiaotong University, Fujian University of Technology, Chang'an University, Shandong University of Science and Technology, Fujian Provincial Key Lab of Big Data Mining and Applications, and the National Demonstration Center for Experimental Electronic Information and Electrical Technology Education (Fujian University of Technology). The conference was intended as an international forum for researchers and professionals engaged in all areas of smart vehicular technology, vehicular transportation, vehicular communication, and applications.
Study on the Algorithm for Train Headway Based on the Simulation of Operation by Driver of High-Speed Railway -- The Connection Mode between Inter-city Rail Transit and Urban Transportation System in Urban Agglomeration -- The Risk Attitude Research on Route Choice Problem in Regional Rail Transit Based on Risk Decision Theory -- The Topological Structure of Chengdu Metro Network Based on Complex Network Theory -- Research on Freights Organization Strategy Based on China-Laos Railway -- Study on the Optimization of Multi-transportation Modes in the Surrounding Area of Subway -- The Analysis Method of Regional Railway Network Capacity Loss under emergent conditions -- Railway Timetable Diagnostic Analysis Based on Train Operation Data -- A Generalized FSM Implementation Framework -- Method on Scale Problem of Passenger Catering Center for High-Speed Railway -- An improved Linear population size reduction based Parameters with Adaptive Learning Mechanism Di erential Evolution (iLPALMDE) for real-parameter single objective black box optimization.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Artificial intelligence; Computational Intelligence; Transportation Technology and Traffic Engineering; Artificial Intelligence